Mast Cells Modulate Antigen-Specific CD8+ T Cell Activation During LCMV Infection - Hackler, Yana; Siebenhaar, Frank; Löhning, Max; Maurer, Marcus; Muñoz, Melba (Frontiers in Immunology, 2021)
Mast cells (MCs), strategically localized at mucosal surfaces, provide first-line defense against pathogens and shape innate and adaptive immune responses. Recent studies have shown that MCs are involved in pathogenic responses to several viruses including herpes simplex viruses, dengue virus, vaccinia virus and influenza virus. However, the underlying mechanisms of MCs in the activation of CD8+ T cells during viral infections are not fully understood. Therefore, we investigate the role of MCs in the development of virus-specific CD8+ T cell responses using the well-characterized murine lymphocytic choriomeningitis virus (LCMV) model and the transgenic MasTRECK mice that contain the human diphtheria toxin receptor as an inducible MC-deficient model. Here, we report that MCs are essential for the activation and expansion of virus-specific CD8+ T cells. After MC depletion and subsequent intradermal LCMV infection, the CD8+ T cell effector phenotype and antiviral cytokine production were impaired at the peak of infection. Importantly, MC-deficient mice were unable to control the infection and exhibited significantly higher viral loads in the spleen and draining lymph nodes compared to that of wild type control mice. In the absence of MCs, dendritic cell (DC) activation was impaired upon LCMV infection. In addition, type-I interferon (IFN) levels in the serum and in the spleen of MC-deficient mice were reduced during the first days of infection. Interestingly, depletion of MCs after intradermal LCMV infection did not impair virus-specific CD8+ T cell expansion, activation or antiviral cytokine production. In summary, our results indicate that MCs play a pivotal role in the activation and antiviral functions of CD8+ T cells through proper DC activation. A better understanding of the impact of MCs on CD8+ T cell responses is mandatory to improve antiviral immune responses.